Sensitization of Perovskite Strontium Stannate SrSnO3 towards Visible-Light Absorption by Doping - Hungru Chen; Naoto Umezawa (International Journal of Photoenergy)
Perovskite strontium stannate SrSnO3 is a promising photocatalyst. However, its band gap is too large for efficient solar energy conversion. In order to sensitize SrSnO3 toward visible-light activities, the effects of doping with various selected cations and anions are investigated by using hybrid density functional calculations. Results show that doping can result in dopant level to conduction band transitions which lie lower in energy compared to the original band gap transition. Therefore, it is expected that doping SrSnO3 can induce visible-light absorption.